The Impact of Generated Information on the Banks Efficiency: Strategic Planning as a Mediator: A Case Study on Al-Tadamon Islamic Bank in Sudan - Enad, Osama Mohamed Ahmed (International Journal of Economics and Financial Issues, 2019)
The main objective of this study is to test the relationship among the generated information and bank’s efficiency; the mediating impact of Strategic planning, the data have been collected from 60 employees and managers of Al-Tadamon Islamic Bank. The Questionnaire was used to collect the data; the overall response rate was 95%. Many statistic tools have been utilized, reliability test, exploratory factor analysis, correlation analysis and hierarchical regression to the goodness of measures and interrelationships. The outcomes revealed that generated information impact on the bank’s efficiency, also strategic planning influence the bank’s efficiency, besides the association between the generated information and Strategic planning Keywords: Generated Information, Banks Efficiency, Strategic Planning JEL Classification: G2 DOI: https://doi.org/10.32479/ijefi.7627